Profit-Loss Sharing versus Interest-Based Contract: A Systematic Review - Gholami, Reza; Aisyah Abdul-Rahman; Nor Ghani Md Nor; Fathin Faizah Said (International Journal of Economics, Management and Accounting, 2021)
Profit-loss sharing contract (PLSC) is a contract that shares business risks between participants, while interest-based contract (IBC) requires entrepreneurs to bear total business risks. Islamic scholars believe that PLSC is fairer and more profitable than IBC besides inducing a more stable economy with lower income gap. Despite the strong belief of PLSC positive impact, market participants (i.e., the government, financial sectors, banking industry, companies, and individuals) still adopt IBC when dealing with financial transactions. The refusal in embracing PLSC has raised many questions regarding PLSC and the superiority of IBC against PLSC. Drawing on multiple literature sets, this study applied a systematic literature review (SLR) methodology by using the snowball sampling method (SSM) to classify the findings based on six main constructs: Fair-Justice, Feasibility, Profitability, PLSC ratio, Stability and ‘Others’ (i.e., definition, evolution, and general comparison). Some 116 studies were found, which rigorously discussed various aspects of IBC and PLSC together, with 70% published after 2001, 80% applied theoretical approach, 36% had been indexed by Web of Science (WoS) and Scopus database, whereby feasibility was the most frequent topic. Despite the positive growth in a number of studies, the literature suffers from a lack of empirical studies.